The dream that failed : reflections on the Soviet Union - Laqueur, Walter, 1921-2018 26.05.1921-30.09.2018 (Oxford Univ. Press, 1994)
The Dream that Failed offers an authoritative assessment of the Soviet era - from the triumph of Lenin to the fall of Gorbachev. In recent years, decades of conventional wisdom about the U.S.S.R. have been swept away, while a flood of evidence from Russian archives demands new thinking about old assumptions. This inquiry is conducted on the grand scale: the author explains how the Bolsheviks won the struggle for power in 1917; how they captured the commitment of a young generation of Russians; why the idealism faded as Soviet power grew; how the system ultimately collapsed; and why Western experts have been wrong about the Communist system. Thoughtful and incisive, Laqueur reflects on the early enthusiasm of foreign observers and Bolshevik revolutionaries for the new Soviet order, then takes a piercing look at the totalitarian nature of the regime